RETRACTED: International practice and cooperation in the interests of sustainable development of the BRICS countries - Suchilina Anna; Korneeva Elena; Krayneva Raisa; Parmanasova Aisulu (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 138, 00001 (2024), https://doi.org/10.1051/bioconf/202413800001